KEPEMIMPINAN TRANSFORMASIONAL MEMODERASI PENGARUH SELF EFFICACY DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU SEKOLAH DASAR KECAMATAN PETUNGKRIYONO KABUPATEN PEKALONGAN (Jurnal Mahasiswa Pasca Sarjana, 2015)
This  study  aimed  to  analyze  and  test  the  Influence  of  Professional  Competence  and Discipline Work on the Performance of elementary school teachers throughout the District Tirto Pekalongan with Organizational Climate moderated.This type of research is a field research (field research), using a quantitative approach. The population in this study is a civil servant teachers in the district elementary Tirto Pekalongan regency totaling 213 teachers. Samples were taken using purposive technique of proportional random sampling, some 139 teachers. Techniques of analysis using multiple linear analysis testing, ² test, and hypothesis testing using t test.  Based on   the results  of  the  study  can  be  summarized  as follows:  professional  competence  has no  effect on teacher  performance,  Work Discipline  positive  and significant impact on  teacher  performance, Climate   Organizational   positive   and   significant   impact   on   teacher   performance,   Climate Organizational Professional Competence to strengthen the influence of teacher performance, and Organizational Climate Work Discipline strengthen the influence of the teachers' performance. Keywords      : professional  competence,  discipline  work,  organizational  climate,  and teacher performance.